Reversible structural isomerisation in rare thioether complexes of cobalt(ii) - Effects of ligand architecture - Evans, John; Levason, William; Manning, Joanna M.; Reid, Gillian; Tsoureas, Nikolaos; Webster, Michael (Dalton Transactions, 2007)
Rare examples of (high spin) Co(ii) complexes with geometrically constrained tetrathioether ligands exhibit a very unusual structural isomerism, switching reversibly between tetrahedral monomers in solution and octahedral chain polymers in the solid; the crystal structures of one polymeric species and a tetrahedral monomer model compound are described. © The Royal Society of Chemistry.